Numerical study of scale effects on self-heating ignition of lithium-ion batteries stored in boxes, shelves and racks. (25th May 2021) - Hu, Zhenwen; He, Xuanze; Restuccia, Francesco; Yuan, Han; Rein, Guillermo
Highlights: Self-heating ignition is studied as possible cause of fire during storage of LIBs. The thermal and chemical behaviour of large ensembles of LIBs are simulated in detailed. The critical ambient temperatures are predicted to decrease with the size of the battery ensemble. Thermal insulation of batteries ensembles is predicted to increase the possibility of self-ignition. Exothermic anode reactions are predicted to be crucial in self-ignition of large battery ensembles. Abstract: The fire safety of Lithium-ion batteries (LIBs) during their storage and transport is becoming of prime importance for the industry, with a number of such fires reported in recent years. It is crucial to understand the mechanisms and causes of these fires to provide insights for prevention. Previous studies mostly focused on small ensembles with a few cells and the chemistry involved. The possibility of ignition resulting from heat transfer within a large-size ensemble of LIBs had received little attention before. Focusing on the fire safety of large-scale stored LIBs, we discuss the risk and likelihood of self-heating ignition, which is a known cause of fires in other industries (e.g. chemical storage). Taking LiCoO2 type of battery as a base case and using its chemical kinetics reported in the literature, we build a transient heat transfer model with multi-step reactions to analyze the self-heating behaviour of ensembles of LIBs. Four typical storage sizes, from a single cell to racks containing around 2 million cells, are simulated using COMSOL Multiphysics. The results show that the critical ambient temperature for self-heating ignition is significantly lower for a large-scale LIB ensemble (e.g. 60 °C for the rack), indicating spontaneous side reactions are not negligible heat sources in large LIB ensembles and self-heating poses potential fire hazards in storage. Effects of size and heat transfer in LIB ignition should therefore not be ignored. This work provides insights into the fire safety of Li-ion batteries and additional means of protection during storage and transport.